Short- and long-term increased risk of all-cause mortality in a tuberculosis cohort attributed to SARS-CoV-2 infection: a time-dependent survival analysis in ChileResearch in context - Vargas-García Salvador; Eduardo A. Undurraga; Nadia Escobar; Christian García; Natalia Vergara; María Elvira Balcells (The Lancet Regional Health. Americas)
Summary: Background: Concurrent tuberculosis (TB) and COVID-19 increases the risk of mortality; however, most studies have focused primarily on short-term outcomes. We assessed the short and long-term impact of TB and SARS-CoV-2 coinfection on all-cause mortality. Methods: We conducted a retrospective nationwide cohort study in Chile, including adults diagnosed with active TB from January 1st, 2020, to December 31st, 2021, with follow-up until November 30th, 2022. SARS-CoV-2 coinfection was defined as occurring from 30 days before to six months after TB diagnosis. Short-term mortality was defined as death within 90 days of TB or TB/SARS-CoV-2 diagnosis, and long-term mortality as death occurring after 90 days. We used a time-dependent Cox survival analysis, adjusting for sociodemographic factors, SARS-CoV-2 vaccination, and relevant comorbidities including HIV, diabetes and Mycobacterium tuberculosis drug-resistance status. Findings: The cohort included 3721 adults (median age: 47 years, interquartile range [IQR]: 32–61); of whom 63·4% were male, and 79·4% had pulmonary TB. The median follow-up was 586 days (IQR: 401–820), with 680 deaths (18·3%) recorded. A SARS-CoV-2 coinfection was identified in 393 individuals (10·5%); the mortality in this group was higher in short-term (≤90 days: 14·5% vs. 11·4%) and long-term (>90 days: 11·5% vs. 5·9%) compared to TB alone. Coinfection increased the risk of all-cause mortality during the entire follow-up (aHR [adjusted Hazard Ratio]: 2·8, 95% CI: 2·26–3·47), over three-fold in the short-term (aHR 3·4, 95% CI: 2·57–4·51) and nearly two-fold in the long-term (aHR: 1·72, 95% CI: 1·18–2·52). Excess mortality persisted beyond the first year (aHR: 2·04, 95% CI: 1·09–3·82). SARS-CoV-2 vaccination reduced mortality risk in the TB cohort by 35% (95% CI: 19–46%). Interpretation: Tuberculosis and SARS-CoV-2 coinfection was associated with significantly increased all-cause mortality in both the short and long-term, with elevated risk persisting beyond TB treatment completion. These findings highlight the need for continued post-treatment follow-up and prioritization of SARS-CoV-2 vaccination among individuals with TB. Funding: ANID-FONDECYT, Chile, and CONAHCYT, Mexico.